INOVASI PELAYANAN PUBLIK (STUDI KASUS PERIZINAN PENANAMAN MODAL di BPPT KOTA SEMARANG) - junior, marten prasetyo; ., purwoko; yuwono, teguh (Journal of Politic and Government Studies, 2016)
AbstractSemarang is the capital of Central Java province. As a big city, investment is required for regional development. One way to increase investment in Semarang is with innovations in investment licensing. The purpose of this research is to find BPPT innovations in investment licensing, how the process of innovation in the BPPT and to identify any obstacles in the innovation of investment services. This study used qualitative research methods to explore and understand the meaning that comes from social problems.The results of this research indicate that there are some innovations in investment service applied in BPPT, process of implementing the innovation of investment services and obstacles in the innovation of investment services. Investment service innovations consisting of process innovation, service innovation and system innovation. For the process of innovation implementing is based on standard operating procedures and instructions from the central government. Furthermore there are four obstacles in the innovation of investment services.Advice given to BPPT institution is the need for monitoring and evaluation of the innovation investment, studying the obstacles that occur in the process of investment licensing service and continue to develop new innovations, especially in the investment service.Keywords : innovation, investment service